2000
DOI: 10.1211/0022357001777405
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Monitoring of Warfarin: the Appropriate Response Marker

Abstract: Warfarin is a 4-hydroxycoumarin anticoagulant drug used for the prevention and management of thromboembolic and vascular diseases. It acts through the inhibition of the vitamin K-dependent transcarboxylation reactions that convert precursors of clotting factors into their active form. Appropriate use of warfarin requires patient monitoring and dosage adjustments, to ensure its safety and efficacy. The aim of this work was to clarify the relationship between traditional (prothrombin time, usually expressed as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Lind et al [14] found, in contrast, that coagulation factor II had a relative little influence on INR. Sarode et al [9] found that in INR above 5.0, only a sparse correlation existed between INR and coagulation factors II and X. Costa et al [10] confirmed this observation, also in patients with INR within therapeutic INR target range. This is in contrast to our findings, in which we found significant association between coagulation factor activities and INR.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Lind et al [14] found, in contrast, that coagulation factor II had a relative little influence on INR. Sarode et al [9] found that in INR above 5.0, only a sparse correlation existed between INR and coagulation factors II and X. Costa et al [10] confirmed this observation, also in patients with INR within therapeutic INR target range. This is in contrast to our findings, in which we found significant association between coagulation factor activities and INR.…”
Section: Discussionmentioning
confidence: 89%
“…Costa et al [10] have reported on a weak relationship between coagulation factors II and X versus the level of INR, and advocated that coagulation factors II and X could be used for optimizing monitoring. Furthermore, D 0 Angelo et al [4] have stated that the activity of coagulation factor II better reflects the antithrombotic effect than the INR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…was 12IU/dL [10][11][12][13][14] in the INR 2-3 group, 9IU/dL [8][9][10][11] in the INR>3-4.5group,and7IU/dL [6][7][8][9]intheINR>4.5group(Kruskal-Wallis test, P<0.0001; Figure 1C)…”
Section: P<00001;figure1b)forfx:cvaluesmedian[interquartile]rangementioning
confidence: 99%
“…Since adverse events are common during oral anticoagulation therapy (Linkins et al , ), maximizing time in a therapeutic range is essential to improve outcomes. In fact, the response to warfarin administration is highly variable and requires close monitoring to ensure its safety and efficacy (Costa et al , ; Wiedermann and Stockner, ).…”
Section: Introductionmentioning
confidence: 99%